Environmentalism beyond Borders: The MT Arman 114 Oil Spill and the Politics of Marine Protection in Indonesia - Alsha Nuraini; Aulya Ananda; Ruben Binsar William Manurung (Jurnal Riksa Cendikia Nusantara, 2025)
The oil spill caused by the MT Arman 114 ship in the North Natuna Sea is a clear example of how marine pollution is a transboundary issue with fatal consequences for the environment, economy, and society. This article analyzes the case from an environmentalism perspective in international relations. Indonesia's blue economy development, which is part of its strategic roadmap, presents a paradox in its implementation, which has yet to clarify the legal status of marine governance. The environmental damage that has occurred in Natuna has had a direct impact on the economy of the local community, most of whom are fishermen. Law enforcement by international regimes such as UNCLOS and MARPOL is also still hampered by loopholes in the flag of convenience. Therefore, there must be long-term environmental restoration based on blue justice, economic compensation, and maritime governance reform